STRATEGIC MANAGEMENT AS A NEW PARADIGM IN DEVELOPING EDUCATIONAL INSTITUTIONS: A LITERATURE REVIEW - Syaharuddin; Maimun (Idaarah: Jurnal Manajemen Pendidikan, 2024)
Facing the challenges of globalization and rapid advancements in the education sector, educational institutions must adapt with effective strategies to enhance their quality and competitiveness. This study aims to analyze the application of strategic management as a new paradigm in the development of educational institutions through a systematic literature review approach. The research employs a qualitative methodology, sourcing literature from Scopus, DOAJ, and Google Scholar, with publications selected from 2014 to 2024. The evaluation results indicate that the implementation of strategic management in educational institutions has a significant impact on improving academic quality, student satisfaction, and global reputation. Strategies based on data, strategic planning, internationalization integration, and Total Quality Management (TQM) have proven effective in enhancing academic outcomes and institutional reputation. Additionally, internal factors such as organizational culture and transformational leadership, along with external factors such as government regulations, technology, and market demands, influence the effectiveness of strategic management. Strategic management models, such as the Balanced Scorecard (BSC) and SWOT analysis, show different relevancies; BSC focuses more on long-term performance measurement, while SWOT analysis is useful for initial analysis and adaptive strategy formulation. This research provides insights into the role of strategic management in improving the quality and competitiveness of educational institutions in the context of globalization and environmental change.